The Activeness and Learning Motivation of MTs Ibnu Sina Students in Ecoprint Learning Using Project-Based Learning Modules - Sugiyem Sugiyem; Salmaa; Evy Halimah (Universitas Pendidikan Ganesha, 2026)
Skill-based learning often faces challenges related to low student motivation and limited engagement in the learning process. This study aims to analyze students’ learning activity and learning motivation in ecoprint learning using a Project-Based Learning (PBL)-based module, as well as to explore factors that support student engagement during the learning process. The study employed a quantitative descriptive approach involving 25 eighth-grade students selected through purposive sampling. Data were collected using a learning activity self-assessment instrument, a learning motivation questionnaire, an open-ended questionnaire, and documentation. Instrument validity was tested using Pearson’s Correlation, while reliability was examined using Cronbach’s Alpha. Data were analyzed using descriptive statistics with high, moderate, and low categories. The findings revealed that most students demonstrated high and moderate levels of learning activity, while learning motivation was predominantly categorized as high. No students were classified in the low category for either aspect. Qualitative findings indicated that affective factors, hands-on activities, and creative-artistic elements were the primary drivers of student engagement. The study suggests that the implementation of a PBL-based ecoprint module is associated with high levels of student motivation and learning activity and has the potential to serve as an alternative approach to skill-based learning that is more meaningful, participatory, and student-centered. These findings imply that integrating authentic projects and creative activities can support the development of engaging learning experiences and encourage active student participation.